2021
DOI: 10.1186/s13027-021-00362-7
|View full text |Cite
|
Sign up to set email alerts
|

Human immunodeficiency virus-related renal cell carcinoma: a retrospective study of 19 cases

Abstract: Purpose We aimed to investigate basic information, clinical findings, treatments for tumor, pathology, and outcomes of HIV-positive patients diagnosed with renal cell carcinoma (RCC). Patients and methods We collected 19 patients from 2012 to 2020 who are diagnosed with RCC with HIV-positive. A retrospective analysis was performed on their hospitalization course and tumor-related parameters, including basic information, clinical findings, HIV-assoc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
(24 reference statements)
0
8
0
Order By: Relevance
“…Zhang and Zhu et al from Beijing Youan Hospital reported 19 HIV-infected patients diagnosed with RCC. They concluded that there was no evidence to support a relationship between immune deficiency and tumor progression, even though some patients did not undergo regular ART (49). Overall, recent studies have tended to consider that there is insufficient evidence to prove an association between HIV-induced immunodeficiency and RCC.…”
Section: Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang and Zhu et al from Beijing Youan Hospital reported 19 HIV-infected patients diagnosed with RCC. They concluded that there was no evidence to support a relationship between immune deficiency and tumor progression, even though some patients did not undergo regular ART (49). Overall, recent studies have tended to consider that there is insufficient evidence to prove an association between HIV-induced immunodeficiency and RCC.…”
Section: Risk Factorsmentioning
confidence: 99%
“…With the use of more imaging techniques, early-stage RCC can be detected incidentally, improving the cure rate and survival time of patients. Some case reports showed that there were no marked differences in pathology between RCC with and without HIV (45,48,49). In 2008, Gaughan et al reported nine RCC patients with HIV, six of whom had ccRCC (45).…”
Section: Histological Diagnosismentioning
confidence: 99%
“…recently found that the clinical characteristics, treatment measures, and pathology of 19 HIV-positive renal cell carcinoma (RCC) patients were similar to those of the general population. 12 Although similar to RCC, HIV-associated kidney cancer has a poor prognosis in an advanced stage and is difficult to detect early due to the lack of molecular biomarkers 13 and the incidence of RCC in the HIV-positive population is greater than that in the non-HIV population. 14 , 15 In a large meta-analysis of seven population-based HIV cancer studies involving more than 400,000 HIV-positive patients, Grulich et al.…”
Section: Introductionmentioning
confidence: 99%
“…As highe ciency combined anti-retrovirus therapy (HAART) is widely used, gradually extend the life of people living with HIV, the incidence of HIV merger other diseases is higher, because HIV CD4 + T lymphocyte number decreasing, and even complete loss reduction in immune function of human cells, lead to all sorts of opportunistic infections and tumors, and It has been reported that HIV infection can be a risk factor for Kaposi's sarcoma and non-Hodgkin's lymphoma 3,4. At the same time, HIV-associated urological tumors have attracted the attention of urology experts. Bladder cancer is the most common urological malignancy and the tenth most common malignancy in the world 5 . In current studies at home and abroad, the correlation between bladder cancer and HIV infection remains unclear.…”
Section: Introductionmentioning
confidence: 99%